A study of the air quality of working areas in foundries - A. M. Lasarenkov (Литьë и металлургия)
The results of the study of air quality on workplaces of foundrymen. The results of measures of dust content and content of harmful substances in the workplace areas at foundries with different nature of production are given. It is noted that the dust content in the air of the working area of the foundry areas exceeds the maximum permissible concentrations at all workplaces, with the largest excess noted in the mass production shops. The highest exposures to dust are castings dressers, cleaners and castings technicians. The harmful substances such as carbon monoxide, nitrogen oxides, phenol, formaldehyde, etc. are also were found in the air of the working zones, the content of which is determined by the applied technological processes.